2021
DOI: 10.52586/5060
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid as a medium of liquid biopsy in the management of patients with non-small-cell lung cancer having central nervous system metastasis

Abstract: The molecular profiling of tumors is fundamental in the management of advanced non-small-cell lung cancer (NSCLC). A tissue specimen obtained from biopsy is needed for diagnosis and mutation analysis. However, this may not be feasible for some metastatic sites, such as central nervous system (CNS) lesions, particularly for repeated biopsy. Liquid biopsy with plasma is an emerging tool for molecular testing and could be a surrogate method if tissue cannot be obtained. However, the use of plasma is limited for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…NSCLC is a malignant lung tumor ( 24 ), and patients with advanced NSCLC have a poor prognosis. In the era of precision cancer therapy, NSCLC treatment includes chemotherapy, immunotherapy, and targeted therapy ( 6 , 25 ). In the existing treatment model, the overall cure rate for NSCLC patients is <20%, and the 5-year survival rate for advanced patients is <5% ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSCLC is a malignant lung tumor ( 24 ), and patients with advanced NSCLC have a poor prognosis. In the era of precision cancer therapy, NSCLC treatment includes chemotherapy, immunotherapy, and targeted therapy ( 6 , 25 ). In the existing treatment model, the overall cure rate for NSCLC patients is <20%, and the 5-year survival rate for advanced patients is <5% ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, these intermediate and advanced patients may also have local recurrence or general metastasis ( 4 ). In recent years, new therapeutic approaches, such as immunotherapy and targeted therapy, have also increased the 5-year survival rate ( 5 , 6 ). However, these current therapeutic approaches are far from sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study showed that the supernatant of cerebrospinal fluid (CSF) in patients with EGFR-mutant NSCLC and leptomeningeal metastasis (LM) is a valuable specimen for EGFR mutation testing, demonstrating that the detection rates of EGFR mutations and T790M in cell-free DNA (cfDNA) of CSF were 68.8%, and 14.6%, respectively. [65] The best way to use CSF for diagnosis, tracking tumor heterogeneity, or treatment guidance requires further investigation [66]. CSF diversion, including ventricular peritoneal shunt, and lumbar peritoneal shunt has been reported to be a useful and safe management for LM and hydrocephalus [67].…”
Section: Egfrmentioning
confidence: 99%
“…Broadly, lung cancer cases are separated into relatively rare small-cell lung cancers and the more common non-small cell lung cancers (NSCLCs), which account for 85–90% of the total caseload ( 2 , 3 ). Although many advances in the treatment and diagnosis of this condition have been made in recent years, NSCLC patients still face relatively poor 5-year overall survival (OS) outcomes ( 4 , 5 ). Platinum-based dual chemotherapy remains the standard approach to treating patients with advanced-stage disease ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%